How did human dwelling and working intensity change over different stages of COVID-19 in Beijing?. (November 2021) - Liu, Yaxi; Pei, Tao; Song, Ci; Chen, Jie; Chen, Xiao; Huang, Qiang; Wang, Xi; Shu, Hua; Wang, Xuyang; Guo, Sihui; Zhou, Chenghu
Highlights: Using mobile phone data to track human activity changes over stages of COVID-19. Human working intensity decreased 60% citywide during COVID-19. Human dwelling intensity decreased 40% in some work and education areas. 43% of residents left Beijing before COVID-19, while only 16% have returned back. All commuters decreased commuting times, while only 75% have reverted to normal. Abstract: The COVID-19 pandemic has changed human daily activities significantly. Understanding the nature, causes, and extent of these changes is essential to evaluate the pandemic's influence on commerce, transportation, employment, and environment, among others. However, existing studies mainly focus on changes to general human mobility patterns; few have investigated changes in specific human daily activities. Based on one-year longitudinal mobile phone positioning data for more than 31 million users in Beijing, we tracked intensity changes in two basic human daily activities, dwelling and working, over the stages of COVID-19. The results show that during COVID-19 outbreak, human working intensity decreased about 60% citywide, while dwelling intensity decreased about 40% in some work and education areas. After COVID-19 was under control, intensity in most regions has recovered, but that in schools, hotels, entertainment venues, and tourism areas has not. These intensity changes at regional scale are due to behavior changes at individual scale: about 43% of residents left Beijing before COVID-19, while only 16% have returned back; all commuters decreased their commuting times during COVID-19, while only 75% have reverted to normal. The findings reveal variations in human activities caused by COVID-19 that can support targeted urban management in the post-epidemic era.